On Oscillations of Solutions of Third-Order Dynamic Equation - Gro Hovhannisyan (Abstract and Applied Analysis)
We are proving the new oscillation theorems for the solutions of third-order linear nonautonomous differential equation with complex coefficients. In the case of real coefficients we derive the oscillation criterion that is invariant with respect to the adjoint transformation. Our main tool is a new version of Levinson's asymptotic theorem.